Lacto-Vegetarian Diet and Correlation of Fasting Blood Sugar with Lipids in Population Practicing Sedentary Lifestyle. Issue 5 (3rd September 2017) - Praharaj, Ardhendu Bhusan; Goenka, Ramesh Kumar; Dixit, Sujata; Gupta, Manoj Kumar; Kar, Shantanu Kumar; Negi, Sapna
ABSTRACT: Rising burden of diabetes in India requires quick intervention that integrates policies and programs for effective prevention and control of disease. This retrospective cross-sectional study was conducted to observe effect of diet in two Indian communities practicing sedentary lifestyle. Fasting blood samples were analyzed for blood sugar, glycated-hemoglobin (HbA1C), and lipid profile. Body mass index (BMI) and waist circumference (WC) measurements were recorded. Diabetes incidence was lower in lacto-vegetarian (1.7%) than in non-vegetarian group (5.3%) despite similar lipid profiles and BMI/WC between the groups. Fasting blood sugar (FBS) was positively correlated with LDL and VLDL levels and negatively correlated with HDL, only in lacto-vegetarian group. Study suggests: (1) Indian lacto-vegetarian diet has beneficial effects on diabetes incidence irrespective of high body weight and sedentary lifestyle; (2) intervention to reduce body lipids, such as lipid-lowering drugs and exercise, may have greater effect in reducing FBS levels in this lacto-vegetarian group.